Antibacterial behavior of halloysite nanotubes decorated with copper nanoparticles in a novel mixed matrix membrane for water purification. Issue 6 (26th August 2015) - Duan, Linlin; Zhao, Qianqian; Liu, Jindun; Zhang, Yatao
Abstract : Poly(4-vinylpyridine) (P4VP) with various molecular weights was grafted onto halloysite nanotubes (HNTs) via reverse atom transfer radical polymerization (RATRP). Abstract : Poly(4-vinylpyridine) (P4VP) with various molecular weights was grafted onto halloysite nanotubes (HNTs) via reverse atom transfer radical polymerization (RATRP). Then copper nanoparticles (Cu NPs) were loaded onto the surface of HNTs by complexation and reduction (Cu NPs@HNTs). Finally, a novel mixed matrix membrane, polyethersulfone (PES) ultrafiltration membrane, containing Cu NPs@HNTs was fabricated via the classical phase inversion method. The results showed that the pure water flux of the hybrid membrane was greatly enhanced, and the maximum could reach as high as 212 L m −2 h −1 . The contact angle and atomic force microscopy (AFM) results indicated that the hydrophilicity of the prepared membranes was improved and the surface became smoother, compared with the virgin membranes. Importantly, the antibacterial test indicated that the hybrid membranes showed good antibacterial activity against E. coli with a high bacteriostasis rate of 94.5%.